Brain translocator protein occupancy by ONO‐2952 in healthy adults: A Phase 1 PET study using [11C]PBR28. Issue 7 (11th March 2017) - Frankle, W. Gordon; Narendran, Rajesh; Wood, Andrew T.; Suto, Fumitaka; Himes, Michael L.; Kobayashi, Michiyoshi; Ohno, Tomoya; Yamauchi, Akinori; Mitsui, Katsukuni; Duffy, Kevin; Bruce, Mark
Abstract: ONO‐2952, a novel antagonist of translocator protein 18 kDa (TSPO), binds with high affinity to TSPO in rat brain and human tumor cell line membrane preparations. This study used the TSPO‐specific PET radioligand [ 11 C]PBR28 to confirm binding of ONO‐2952 to brain TSPO in human subjects, and evaluate brain TSPO occupancy and its relationship with ONO‐2952 plasma concentration. Sixteen healthy subjects received a single oral dose of 200, 60, 20, or 6 mg ONO‐2952 ( n  = 4 per dose). Two PET scans with [ 11 C]PBR28 were conducted ≤7 days apart: at baseline and 24 h after ONO‐2952 administration. [ 11 C]PBR28 regional distribution volume ( V T ) was derived with kinetic modeling using the arterial input function and a two tissue compartment model. Nonspecific binding ( V ND ) was obtained on an individual basis for each subject using linear regression as the x ‐intercept of the Lassen plot. The binding potential relative to V ND (BPND ) was derived as the difference between V T in the ROI ( V T ROI) and V ND, normalized to V ND ; BPND  = ( V T ROI – V ND )/ V ND . TSPO occupancy was calculated as the change in BPND (ΔBPND ) from individual's baseline scan to the on‐medication scan to the baseline BPND value. TSPO occupancy by ONO‐2952 was dose dependent between 20–200 mg, approaching saturation at 200 mg both in the whole brain and in 15 anatomic regions of interest (ROI). Estimated Ki values ranged from 24.1 to 72.2 nM. This open‐label, single‐center, single‐dose study demonstrated engagement of ONO‐2952 to brain TSPO. The relationship between pharmacokinetics and TSPO occupancy observed in this study support the hypothesis that ONO‐2952 could potentially modulate neurosteroid production by binding to brain TSPO. Abstract : This open‐label, single‐center, single‐dose study demonstrated engagement of ONO‐2952 to brain TSPO. The relationship between pharmacokinetics and TSPO occupancy observed in this study support the hypothesis that ONO‐2952 could potentially modulate neurosteroid production by binding to brain TSPO.